Fast fault-tolerant control of electric power steering systems in the presence of actuator fault. (October 2019) - Allous, Manel; Mrabet, Kais; Zanzouri, Nadia
Electric power steering is an advanced steering system that uses an electric motor to improve steering comfort of the car. As a result, the failures in the electric motor can lead to additional fault modes and cause damage of the electric power steering system performance. Hence, to ensure the stability of this latter, the present paper proposes a new method to reconfigure the fault control. A novelty approach of fast fault estimation based on adaptive observer is also proposed. Moreover, to guarantee optimal and fast control, a fault-tolerant control based on inverse bond graph modeling is designed to construct the behavior of the nominal system. The simulation and the experimental results on a real electric power steering system reveal the importance of the control strategy and show that the proposed approach works as intended.